Extractive Spectrophotometric Determination of Balsalazide in Pure Form and Pharmaceutical Formulations by Using Safranin-O and Methylene Blue - Naveen Kumar, G.S.; Manohara, Y.N.; Hedge, Karunakar (Asian Journal of Chemistry, 2010)
Two simple extractive spectrophotometric methods are described for the determination of balsalazide in pure form and pharmaceutical formulations. These methods are based on the formation of ion association complexes of the balsalazide with basic dyes safranin-O (method A) and methylene blue (method B) in basic buffer of pH 9.8 followed by their extraction in chloroform. The absorbance of the chloroform layer for each method was measured at its appropriate λmax against the reagent blank. These methods have been statistically evaluated and are found to be precise and accurate.